Analysis Strategies Using Social Media as Strategy to Attract Tourists in Setigi - Tarisa Eka Syafitri; Moh. Agung Surianto (Universitas Muhammadiyah Gresik, 2022)
ABSTRACT This research aims to analyze the social media as a strategy to attract tourists in Setigi. The research method used in this research is a qualitative descriptive approach. The results of the research analysis of strategies for using social media as a strategy to attract tourist in Setigi, various social media platforms as a place for Setigi publications through facebook fanpage, instagram advertising, and tiktok. Facebook and instagram accounts are connected directly with the aim of facilitating the dissemination of content and information by utilizing features that support to attract tourist including re-post, tags, hashtags, caption, instagram story, facebook story. The existence of a timeline of content updates on a regular basis make followers interest stronger, with this an insight feature that can control post and know account performance, so that they can control the promotions that are carried out to be more effective and relevant. The existence of the share feature makes it easier for users to share with each other, Setigi makes a policy that all employees share and upload about Setigi on each employee’s social media platform so that dissemination can be faster. Key words: Setigi, Social Media, Management of Setigi, Tourist.